Crystal structure of 2,2-dichloro-1-(piperidin-1-yl)ethanone - Schwierz, Markus (Acta Crystallogr E Crystallogr Commun, 2015)
In the title compound, C(7)H(11)Cl(2)NO, the piperidine ring shows a chair conformation and the bond-angle sum at the N atom is 359.9°. The H atom of the dichloromethyl group is in an eclipsed conformation with respect to the carbonyl group (H—C—C=O = −5°). In the crystal, inversion dimers are linked by pairs of C—H⋯O hydrogen bonds between the dichloromethyl group and the carbonyl O atom, which generate R (2) (2)(8) loops. The dimers are linked into a ladder-like structure propagating in the [100] direction by short O⋯Cl [3.1084 (9) Å] contacts.